Psychosocial health and psychological adjustment in adolescents and young adults with congenital melanocytic nevi: Analysis of self-reports - Masnari, Ornella; Neuhaus, Kathrin; Schiestl, Clemens; Landolt, Markus A. (Frontiers in Psychology, 2022)
This study assessed self-reported health-related quality of life and psychological adjustment in 43 adolescents and young adults (ages in years: 14- 24, M = 17.6, SD = 2.2) with congenital melanocytic nevi (CMN) and examined associations with sociodemographic variables, characteristic of the CMN, perceived social reactions, and cognitive emotion regulation strategies. Outcome measures included the Pediatric Quality of Life Inventory and the Strengths and Difficulties Questionnaire. Findings suggest impaired psychosocial health and psychological adjustment in youth with CMN compared to community norms. Impairments were associated with higher age of participants, lower socioeconomic status, visibility of the skin lesion, perceived stigmatization, poorer perceived social support, and maladaptive cognitive emotion regulation strategies (self-blame, rumination, and catastrophizing), but not with sex of participants, extent of the skin lesion, and surgical removal of the nevus. Implications for clinical practice and future research are discussed.